In vitro elimination of epidermal growth factor receptor‐overexpressing cancer cells by CD32A‐chimeric receptor T cells in combination with cetuximab or panitumumab. Issue 1 (12th October 2019) - Caratelli, Sara; Arriga, Roberto; Sconocchia, Tommaso; Ottaviani, Alessio; Lanzilli, Giulia; Pastore, Donatella; Cenciarelli, Carlo; Venditti, Adriano; Del Principe, Maria Ilaria; Lauro, Davide; Landoni, Elisa; Du, Hongwei; et al.
Abstract : Cetuximab and panitumumab bind the human epidermal growth factor receptor (EGFR). Although the chimeric cetuximab (IgG1) triggers antibody‐dependent‐cellular‐cytotoxicity (ADCC) of EGFR positive target cells, panitumumab (a human IgG2) does not. The inability of panitumumab to trigger ADCC reflects the poor binding affinity of human IgG2 Fc for the FcγRIII (CD16) on natural killer (NK) cells. However, both human IgG1 and IgG2 bind the FcγRII (CD32A) to a similar extent. Our study compares the ability of T cells, engineered with a novel low‐affinity CD32A 131R ‐chimeric receptor (CR), and those engineered with the low‐affinity CD16 158F ‐CR T cells, in eliminating EGFR positive epithelial cancer cells (ECCs) in combination with cetuximab or panitumumab. After T‐cell transduction, the percentage of CD32A 131R ‐CR T cells was 74 ± 10%, whereas the percentage of CD16 158F ‐CR T cells was 46 ± 15%. Only CD32A 131R ‐CR T cells bound panitumumab. CD32A 131R ‐CR T cells combined with the mAb 8.26 (anti‐CD32) and CD16 158F ‐CR T cells combined with the mAb 3g8 (anti‐CD16) eliminated colorectal carcinoma (CRC), HCT116 FcγR+ cells, in a reverse ADCC assay in vitro . Crosslinking of CD32A 131R ‐CR on T cells by cetuximab or panitumumab and CD16 158F ‐CR T cells by cetuximab induced elimination of triple negative breast cancer (TNBC) MDA‐MB‐468 cells, and the secretion of interferon gamma and tumor necrosis factor alpha. Neither cetuximab nor panitumumab induced Fcγ‐CR T antitumor activity against Kirsten rat sarcoma (KRAS)‐mutated HCT116, nonsmall‐cell‐lung‐cancer, A549 and TNBC, MDA‐MB‐231 cells. The ADCC of Fcγ‐CR T cells was associated with the overexpression of EGFR on ECCs. In conclusion, CD32A 131R ‐CR T cells are efficiently redirected by cetuximab or panitumumab against breast cancer cells overexpressing EGFR. Abstract : What's new? The role of antibody‐dependent cellular cytotoxicity in the antitumor activity of tumor antigen‐specific monoclonal antibodies has stimulated interest in genetically engineering T cells with the CD16 chimeric receptor (CD16‐CR). Here, the authors expand the application of this methodology to triple negative breast cancer (TNBC) overexpressing EGFR by utilizing a novel CD32A 131R ‐CR in combination with anti‐EGFR mAbs. The study supports the use of CD32A 131 R ‐CR T cells combined with either panitumumab or cetuximab—an IgG2 and IgG1 monoclonal antibody, respectively—for targeting TNBC cells overexpressing EGFR. The results may be utilized as a platform for designing therapies targeting TNBC overexpressing EGFR.